A discrete transcriptional silencer in the bam gene determines asymmetric division of the Drosophila germline stem cell. - Chen, D.; McKearin, D.M. (Development, 2003)
The Drosophila germline lineage depends on a complex microenvironment of extrinsic and intrinsic factors that regulate the self-renewing and asymmetric divisions of dedicated stem cells. Germline stem cells (GSCs) must express components of the Dpp cassette and the translational repressors Nanos and Pumilio, whereas cystoblasts require the bam and bgcn genes. Bam is especially attractive as a target of GSC differentiation factors because current evidence indicates that bam is both necessary and sufficient for cystoblast differentiation. In this paper, we have sought to distinguish between mutually exclusive transcriptional or post-transcriptional mechanisms as the primary regulators of bam expression in GSCs and cystoblasts. We find that bam transcription is active in young germ cells but is repressed specifically in GSCs. Activation depends on a 50 bp fragment that carries at least one germ cell-specific enhancer element. A non-overlapping 18 bp sequence carries a transcriptional silencer that prevents bam expression in the GSC. Promoters lacking this silencer cause bam expression in the GSC and concomitant GSC loss. Thus, asymmetry of the GSC division can be reduced to identifying the mechanism that selectively activates the silencer element in GSCs.